Existence of solutions for a class of BVPs on the half-line - Souad Ayadi; Ozgur Ege (Miskolc Mathematical Notes)
In this paper, we establish sufficient conditions to guarantee some existence results of nontrivial solutions for a class of nonlinear boundary value problem posed on an unbounded interval of ℝH1(0,∞)Cl,p ( [0,+∞))